Surgical Approaches to Soft Tissue Infections in Disaster and Earthquake Treatment - Yalçın, Can Ege; Demiröz, Anıl (Cerrahpaşa Medical Journal, 2023)
Soft tissue injuries are common following disasters. Even without disruption of tissue integrity, crush-type traumas can be complicated by secondary infections. Systemic signs should be alerting for generalizing progressive infections. When suspected, except for localized abscesses or cellulitis, debridement, surgical incision, and drainage are necessary. Cite this article as: Yalçın CE, Demiröz A. Surgical approaches to soft tissue infections in disaster and earthquake treatment. Cerrahpaşa Med J. 2023;47(S1):52-53.